Analisis Beban Kerja Mental Petugas Airport Operational Landside And Terminal (AOLT) Di Bandara Internasional I Gusti Ngurah Rai - I Made Wahyu Adhi Nugraha; Suprapti Suprapti (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Excessive workload is one of the triggers for problems in terms of occupational health and safety. Many factors can cause excessive workload, both individual factors and external factors. The workload is divided into two, mental workload and physical workload. In actual practice, it is still common to find employees who experience excessive workload, whether it is experienced simultaneously or under certain conditions. The combination of the G20 Summit event and the year-end holiday season, made all task units at I Gusti Ngurah Rai International Airport very busy. Therefore, analyzing a workload needs to be done as material for consideration and evaluation, which is helpful for later. Mental workload analysis in this study used the NASA-TLX method, with a descriptive quantitative research design. The results showed that of the 28 officers who were analyzed under normal conditions, 14 were in the high category, 12 were in the medium category, and 2 were in the low category, while under certain conditions, 5 were in the very high category, 22 were in the high category, and 1 was in the low category. The mental workload of officers under certain conditions increases significantly compared to normal conditions..